Professional Competency Profile of San Marcos psychologist - Orellana Manrique, Oswaldo (2007)
Taking as reference the project Tuning, research inquires about the recognition of skills generic psychologist from his identification done by students for a fifth year of the period of intership or pre-professional practice and graduates, presenting the outcome of the five powers elected overwhelmingly, establishing their differentiation and relevance.